2018
DOI: 10.2754/avb201887020109
|View full text |Cite
|
Sign up to set email alerts
|

Acute responses of iron indices in Quarter Horses during a 3-barrel racing exercise

Abstract: Energy metabolism and physical performance are dependent on sufficient iron metabolism. Therefore, studies evaluating the iron profile are necessary to elucidate this trace mineral requirements and its role in the equine exercise physiology. The aim of this study was to evaluate the influence of barrel racing exercise on serum iron profile of Quarter horses. Twenty-two regularly trained Quarter horses (8 females and 14 males, 4.8 ± 2.4 years old, mean body weight 431.7 ± 33.9 kg) were enrolled in this study wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Assessments of iron concentration were done in two groups of pull vaquejada horses, one that regularly performed with professional cowboys and in another group with amateur cowboys, and no variations in iron concentration were observed in each group or between groups after a vaquejada simulation test with three races [46]. On the other hand, in another study with three-barrel horses, an increase in serum iron was observed after a race but retuned to baseline val-ues at 30 minutes of recovery [47]. When comparing exercises of different intensities, iron concentrations were found to vary in response to intense and moderate workouts, but no differences between the two intensity levels were found when samples were collected 12-and 24 hours post-exercise [43].…”
Section: Discussionmentioning
confidence: 93%
“…Assessments of iron concentration were done in two groups of pull vaquejada horses, one that regularly performed with professional cowboys and in another group with amateur cowboys, and no variations in iron concentration were observed in each group or between groups after a vaquejada simulation test with three races [46]. On the other hand, in another study with three-barrel horses, an increase in serum iron was observed after a race but retuned to baseline val-ues at 30 minutes of recovery [47]. When comparing exercises of different intensities, iron concentrations were found to vary in response to intense and moderate workouts, but no differences between the two intensity levels were found when samples were collected 12-and 24 hours post-exercise [43].…”
Section: Discussionmentioning
confidence: 93%